Leukocyte immunoglobulin-like receptors in human diseases: an overview of their distribution, function, and potential application for immunotherapies. Issue 2 (28th March 2017) - Zhang, Jilu; Mai, Sunny; Chen, Hui-Ming; Kang, Kyeongah; Li, Xian Chang; Chen, Shu-Hsia; Pan, Ping-Ying
Abstract : Review of how LILRs modulate plasticity of myeloid cell function, and control human diseases. Abstract: Myeloid-derived suppressor cells (MDSCs), a population of immature myeloid cells expanded and accumulated in tumor-bearing mice and in patients with cancer, have been shown to mediate immune suppression and to promote tumor progression, thereby, posing a major hurdle to the success of immune-activating cancer therapies. MDSCs, like their healthy counterparts, such as monocytes/macrophages and granulocytes, express an array of costimulatory and coinhibitory molecules as well as myeloid activators and inhibitory receptors, such as leukocyte immunoglobulin-like receptors (LILR) A and B. This review summarizes current findings on the LILR family members in various diseases, their potential roles in the pathogenesis, and possible strategies to revert or enhance the suppressive function of MDSCs for the benefit of patients by targeting LILRs.